Flow projection for Paraíba do Sul river basin and water availability study from IPCC scenarios - Amancio, Erick Santana (2020)
The Paraíba do Sul river basin is important for the metropolitan region of Rio de Janeiro and São Paulo, in terms of water supply, due to its multiple uses. The present study aims to identify the main impacts of climate change on water availability in the basin upstream of the Funil Reservoir (BMRF), which contains the equivalent reservoir of the Paraíba do Sul River basin, charged with water supply in the Metropolitan Region of Rio de Janeiro. To model the basin, the Monthly SMAP model was used, characterized by being concentrated and mathematical conceptual. The climatic scenarios used were RCP 2.6, 4.5 and 8.5 provided by both the MIROC-ESM and GFDL-CM3 models. The projected precipitation data served to estimate the flow and from this, the 30-year moving averages for each scenario and flow anomalies between 2011 and 2100 were analyzed. It was observed, in general, that the average flows tend to be lower in all scenarios from the 2070s.